Effects of delayed steroid implanting on health, performance, and carcass quality in high health risk, auction market sourced feedlot steers - Munson, Robert D. (Kansas State University, 2015)
Auction derived feeder calves (n=1,601; initial BW = 273.5 ± 4.7 kg) were used to examine the effects of delayed administration of the initial steroid implant on health, performance, and carcass characteristics of feedlot cattle. Steers were procured from multiple-source auction markets in the southeastern United States and shipped to a central Kansas feedyard over a 6 week period from December 2009 to January 2010. Steers were rested overnight prior to processing, then were randomly assigned, within arrival block, to 1 of 2 treatments: 1) implanted with Revalor-XS (40 mg estradiol and 200 mg trenbolone acetate) immediately upon arrival (ARRIVAL); or 2) implanted with the same implant after 45 d (DELAYED). Cattle were weighed on a group scale immediately following processing of each block. Feed deliveries were measured using load cells on feed trucks and recorded daily. Cattle were evaluated daily for morbidity and mortality by trained feedyard health personnel. Sick or injured cattle were removed from the home pen for further diagnosis and treatment. Individual animal health data were obtained and recorded daily. Final BW was calculated by dividing HCW by the average dressing percent of the pen. Carcass data (quality grade and yield grade) were obtained by USDA personnel; presence of lung lesions, pleural adhesions, and liver abscesses was evaluated by trained university personnel. Delaying the initial implant tended to reduce morbidity (24.7 vs. 28.5%; P = 0.13) and reduced railer rates (1.8 vs. 3.3%; P = 0.02); however, there were no effects of timing of implant administration (P ≥ 0.31) on rates of retreatment, mortality, lung lesions, or pleural adhesions. Implanting immediately upon feedlot arrival resulted in numerical improvements in ADG and feed conversion, but these differences were not statistical (P ≥ 0.56). Cattle implanted upon arrival had numerically greater HCW and yield grade vs. cattle implanted on d 45; however, these differences were not statistical (P ≥ 0.16). Delaying the initial implant 45 d did not influence animal health, performance parameters or carcass characteristics in high risk feeder calves.
Keywords: Beef cattle; Carcass; Delayed; Feedlot; Health; Implant; Animal Diseases (0476); Animal Sciences (0475); Veterinary Medicine (0778)